Trends in bovine population in Himachal Pradesh - CHAUHAN, S K (The Indian Journal of Animal Sciences, 2013)
Bovines account for 56% of livestock wealth in Himachal Pradesh against the national figure of 63% during 1987. The findings of study based on secondary data revealed that buffalo population increased at a faster rato that cattle. The growth rate in former (2.03% per annum) was almost 4 times that of latter (0.50% per annum) during 1966-92. A significant proportion of the female bovine population was dry in both the groups, though the lactating efficiency of buffaloes was higher than of cattle in all the census years, Buffalo population dominated the scene in Billaspur, Hamirpur and Una districts. The buffalo-cattle ratio and bovine density was highest in Hamlrpur district of Himachal Pradesh. Average daily milk yield of crossbred cow was almost twice the Indigenous cow: however, buffalo daily milk yield of 2Â 861 g was quite close to the crossbred cow. The proposrtion of crossbred cattle in total cattle population of Himachal Pradesh was 13.01% during 1992. The projected bovine population in Himachal Pradesh would be 2,92 and 3.01 million in 1997 and 2002 respectively, Morecover the shift would be in favour of buffaloes as against cattle due to increasing trend of growth rate in the former and declining trend in the latter.